Serology reveals micro-differences in Plasmodium falciparum transmission in the Hohoe municipality of Ghana - Kyei-Baafour, Eric; Kusi, Kwadwo A.; Oppong, Mavis; Frempong, Abena F.; Aculley, Belinda; Ofori, Ebenezer A.; Theisen, Michael; Kweku, Margaret; Adu, Bright; Hviid, Lars; Ofori, Michael F. (Frontiers in Parasitology, 2023)
Abstract With the decline in malaria transmission due to global efforts, a more sensitive tool is needed to monitor transmission intensity and pattern at the micro-level. Though transmission in a broader area may be similar, factors such as sanitation, practices of open water storage, early morning and evening activities, outdoor sleeping and agricultural practices within communities could cause differences in exposure and thus transmission. This study thus probed malaria transmission at a micro-level using serology in the Hohoe Municipality of Ghana. This cross-sectional study involved 327 asymptomatic children aged 1-12 years in both rural (196) and urban (131) communities in the Hohoe municipality. Total IgG responses specific for three P. falciparum antigens (CSP, MSP2-FC27, MSP2-3D7) were determined in plasma eluted from dried blood spots using indirect ELISA. A higher proportion of individuals in the rural area had parasites by both microscopy and PCR. Total IgG levels and seroprevalence were higher in rural compared to urban communities (p<0.05). In a multiple regression model, adjusting for confounders, levels of PfMSP2-3D7-specific IgG was associated with the higher transmission which occurs in the rural community. The results suggest that though the district is categorized as having medium malaria transmission, differences within settlements may influence malaria transmission reflecting in antibody levels and prevalence of malaria antigen-specific IgG.